Temporal changes in prevalence and severity of pulmonary hypertension, and relationship to outcomes in coarctation of aorta - Ahmed Younis; Yogesh N.V. Reddy; William R. Miranda; Ahmed T. Abdelhalim; Barry A. Borlaug; Heidi M. Connolly; Alexander C. Egbe (International Journal of Cardiology: Heart & Vasculature)
Background: Pulmonary hypertension (PH) affects 20% of adults with coarctation of aorta (COA). What is not known is whether PH prevalence and severity increased over time, and the prognostic implications of such changes. The purpose of this study was to assess temporal changes in PH prevalence and severity (PH progression), and to determine the correlates and prognostic implications of pH progression in adults with COA. Method: Retrospective cohort study of adults with repaired COA with ≥ 2 echocardiograms > 5 years apart. PH was defined as Doppler-derived right ventricular systolic pressure (RVSP) > 40 mmHg. Results: Of 392 patients (age 35 years [24–49]; females 154 [39 %]), median RVSP was 30 (26–35) mmHg, and 76 (19 %) had PH at baseline echocardiogram. There was a temporal increase in PH severity (ΔRVSP 6 ± 9 mmHg, p = 0.008), and PH prevalence (19 % versus 27 %, p = 0.01). The correlates of Δ RVSP were older age, left atrial (LA) dysfunction, left ventricular (LV) hypertrophy, high LV global afterload, and atrial fibrillation. Of 392 patients, 50 (13 %) died, and Δ RVSP was associated with mortality (adjusted hazard ratio 1.19 [1.08–1.31] per 5 mmHg increase, p = 0.006) after adjustment for baseline RVSP, demographic indices, comorbidities, and echocardiographic indices. Conclusions: These findings underscore the clinical importance of pH in COA and supports the need for new strategies for prevention and treatment of LA and LV dysfunction, which should in turn, slow the pace of pH progression in this population. Such strategies should include early detection and treatment of hypertension and atrial fibrillation.